2015
DOI: 10.1080/13670050.2015.1087962
|View full text |Cite
|
Sign up to set email alerts
|

Facilitative effects of learner-directed codeswitching: evidence from Chinese learners of English

Abstract: Facilitative effects of learner-directed codeswitching: Evidence from Chinese learners of EnglishThis study examines the interaction between learner-oriented codeswitching (CS) practices and the degree to which intermediate Chinese L2 learners of English engage in classroom interaction. The guiding questions are whether the teacher's CS use facilitates classroom interaction at moderate L2 proficiency, and if so, at which specific stages of the lesson, and to what extent. A systematic comparison of two class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 32 publications
2
9
0
Order By: Relevance
“…The students had difficulty understanding new language item and challenging concepts in L2. These findings are compatible with many previous research outcomes (e.g., Bensen & Çavuşoğlu, 2013;Hall & Cook, 2012;Zhu & Vanek, 2017). Cahyani et al (2018) clearly stated that the teachers' CS helped students to understand unfamiliar concepts when the focus was on the subject matter rather than the language itself.…”
Section: Functions Of Teacher's Cssupporting
confidence: 91%
See 1 more Smart Citation
“…The students had difficulty understanding new language item and challenging concepts in L2. These findings are compatible with many previous research outcomes (e.g., Bensen & Çavuşoğlu, 2013;Hall & Cook, 2012;Zhu & Vanek, 2017). Cahyani et al (2018) clearly stated that the teachers' CS helped students to understand unfamiliar concepts when the focus was on the subject matter rather than the language itself.…”
Section: Functions Of Teacher's Cssupporting
confidence: 91%
“…Other studies, however, focused on the practicality and the effectiveness of CS in EFL classrooms (Bahous et al, 2014;Bensen & Çavuşoğlu, 2013;Macaro, 2009;Zhao & Macaro, 2016;Zhu & Vanek, 2017). The overall results did not provide any evidence that teacher's CS was harmful to the acquisition of lexical items.…”
Section: Functions and Practicality Of Teacher's Csmentioning
confidence: 67%
“…Little attention has been paid to the effectiveness of L1 on L2 learning among the 15 reviewed studies, only Zhu & Vanek (2015) found that a higher student response frequency as well as a longer mean utterance length in code-switching classes than L2-only classes. The participants were divided into two groups: two code-switching classes formed 'the experimental group', and two L2-only classes were 'the control group'.…”
Section: The Effectiveness Of L1 Use On L2 Learningmentioning
confidence: 99%
“…On the other hand, based on many arguments to support their position, a great number of researchers suggest that banning L1 totally from an L2 classroom does not seem realistic (Mayo & Hidalgo, 2017;Zhu & Vanek, 2015). Rather than being an obstacle to language learning, L1 use may take place as a useful cognitive tool that helps to connect the new learning concept with preexisting knowledge and thus facilitates the learning process and promotes linguistic production (Codina Camó & Pladevall Ballester, 2015;Zhu & Vanek, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, based on many arguments to support their position, a great number of researchers suggest that banning L1 totally from an L2 classroom does not seem realistic (Mayo & Hidalgo, 2017;Zhu & Vanek, 2015). Rather than being an obstacle to language learning, L1 use may take place as a useful cognitive tool that helps to connect the new learning concept with preexisting knowledge and thus facilitates the learning process and promotes linguistic production (Codina Camó & Pladevall Ballester, 2015;Zhu & Vanek, 2015). Besides warning about the domination of L1 in L2 classrooms , many researchers claim that playing an essential role in diminishing learning anxiety, the use of L1 may also help to create a more comfortable and effective learning atmosphere, particularly for shy or less-proficient L2 learners to communicate in the classroom (Rolin-Ianziti & Varshney, 2008;Nation, 2003).…”
Section: Introductionmentioning
confidence: 99%